2015
DOI: 10.1016/j.ijppaw.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Manifold habitat effects on the prevalence and diversity of avian blood parasites

Abstract: Habitats are rapidly changing across the planet and the consequences will have major and long-lasting effects on wildlife and their parasites. Birds harbor many types of blood parasites, but because of their relatively high prevalence and ease of diagnosis, it is the haemosporidians – Plasmodium, Haemoproteus, and Leucocytozoon – that are the best studied in terms of ecology and evolution. For parasite transmission to occur, environmental conditions must be permissive, and given the many constraints on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
143
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 119 publications
6
143
0
8
Order By: Relevance
“…In spite of the significance of avian malaria and other haemosporidians as wildlife pathogens, only a few studies have addressed how their prevalence changes in relation to anthropogenic habitat disturbances, and these studies revealed highly contrasting results (Sehgal 2015). Some documented a higher prevalence of blood parasites in degraded forests compared to undisturbed primary forests (Chasar et al 2009, Ferreira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the significance of avian malaria and other haemosporidians as wildlife pathogens, only a few studies have addressed how their prevalence changes in relation to anthropogenic habitat disturbances, and these studies revealed highly contrasting results (Sehgal 2015). Some documented a higher prevalence of blood parasites in degraded forests compared to undisturbed primary forests (Chasar et al 2009, Ferreira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…). While the environment undoubtedly influences pathogen infections (Budria & Candolin ; Sehgal ), hosts often carry multiple pathogens whose interactions can alter infection dynamics (Cattadori, Boag & Hudson ; Johnson & Hoverman ). Infection with one pathogen can increase a host's susceptibility to other pathogens or to harmful disease (Bordes & Morand ).…”
Section: Introductionmentioning
confidence: 99%
“…Haematozoans are strongly driven by environmental factors, such as temperature and habitat, that can limit parasite development or vector distributions (Rogers et al . ; Santiago‐Alarcon, Palinauskas & Schaefer ; Freed & Cann ; Sehgal ). However, haematozoan infections may also be influenced by biotic parasite interactions (Su et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to known mediators of carry-over effects such as winter habitat, immune defence and parasite pressure also play important roles in migratory strategies (Piersma 1997, Møller & Erritzøe 1998, Altizer et al 2011, Hill et al 2012, Clark et al 2016. Email: clopez25@us.es lines, it has been shown that for some migratory birds, the diversity of their haemosporidian parasites is higher in the tropical wintering grounds than in the temperate breeding areas (review in Sehgal 2015). Email: clopez25@us.es lines, it has been shown that for some migratory birds, the diversity of their haemosporidian parasites is higher in the tropical wintering grounds than in the temperate breeding areas (review in Sehgal 2015).…”
mentioning
confidence: 99%
“…Thus, migratory behaviour may have evolved as a means to escape from this higher pressure of parasites at the wintering grounds (Møller & Sz ep 2010). Furthermore, it is well known that certain habitat features such as temperature, rainfall and vegetation cover are intimately linked to the distribution and abundance of parasite vectors and hence to the prevalence of haemosporidians throughout the world (Mendes et al 2005, Lourenc ßo et al 2011, Cornuault et al 2013, Oakgrove et al 2014, Roiz et al 2015, Sehgal 2015. Furthermore, it is well known that certain habitat features such as temperature, rainfall and vegetation cover are intimately linked to the distribution and abundance of parasite vectors and hence to the prevalence of haemosporidians throughout the world (Mendes et al 2005, Lourenc ßo et al 2011, Cornuault et al 2013, Oakgrove et al 2014, Roiz et al 2015, Sehgal 2015.…”
mentioning
confidence: 99%